The experiences of mental healthcare users regarding the quality of their major depressive disorder treatment - Frans M. Lekoloane; Marang T. Mamahlodi (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Millions of people worldwide are affected by major depressive disorder (MDD). However, those with MDD do not receive treatment. More studies have been conducted on the efficacy of medications rather than the subjective experiences of mental healthcare users (MHCUs).